ANALISIS SWOT SEBAGAI DASAR PERUMUSAN DAN PENERAPAN STRATEGI PADA PERUSAHAAN (Studi Kasus di Telkom Malang) - ani, Erwi; Sudarma, Made (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to determine the internal and external conditions faced by Telkom Malang as the basis for determining the appropriate strategic alternatives for the company. Conditions include the company's internal strengths and weaknesses. While external conditions include the company's opportunities and threats. The method used in this research is descriptive qualitative case study approach. Primary and secondary data is processed to gather information about the strengths and weaknesses and the opportunities and threats of the Telkom Malang. The information obtained was processed using EFE Matrix, IFE Matrix, SWOT Matrix, IE Matrix, and QSPM Matrix. From the analysis of EFE and IFE, EFE matrix Telkom Malang has a total score of 2.758 while IFE matrix Telkom Malang has a total score of 3.022. Position in IE quadrant matrix determined from the total score of IFE matrix as the x-axis and the EFE total score as the y-axis matrix. From the results of this analysis, the position of Telkom Malang is in quadrant IV. This position indicates Telkom Malang in a position to grow and develop (grow and built). The strategy could be applied include intensive strategy (market penetration, market development, and product development) or integrative (backward integration, forward integration, and horizontal integration). Based on the analysis of the matrix QSPM, Telkom Malang can use market penetration strategy. This strategy is considered the most appropriate strategy to be made by Telkom Malang in the face of environmental changes that occurred. Â  Keywords: SWOT analysis, strategy formulation, strategy implementation